Polexandre (732-1632) : repentirs uchroniques - Delphine Amstutz (Les Grandes Figures Historiques dans les Lettres et les Arts, 2022)
What if Uchronia had been invented during the 17th Century? In the novel Polexandre, Marin Le Roy de Gomberville recycled an old project of his, i.e. a chronicle of the Last Valois Kings, mixing facts and fiction with a lot of freedom. As he stated in Le Discours sur les Vices et les Vertus de l’Histoire (Discourse on the vices and virtues of History), true history could offend and had to be transformed. Invention is based on a “normalized narrative of the real past” (Singles). Parallels between past and present enable the writer to express regrets and to imagine plausible divergent histories, directly influenced by the preoccupations of the time. The narration questions the foundation of History itself and of the received identity of famous historical figures.